INTRODUCTION TO MATHEMATICAL FIGURES FOR CHANGING POWER LEARNING MATHEMATICS FOR VOCATIONAL SCHOOL STUDENTS - Mailisman, Nashrullah; Authary, Nailul; Nazariah, Nazariah; Fitriyasni, Fitriyasni; Alfarisyi, M. (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2024)
Applying the history of mathematics in learning is a tool (history as a tool) or strategy for building meaningful and value-laden learning. Nowadays, we often encounter mathematics learning that only emphasizes the use of formulas without paying attention to the beneficial aspects of the material being taught. Educators argue that students must achieve material targets according to predetermined bills. The result is that children study mathematics for years but are still "blind" to mathematics. Mathematics is the mother of world civilization, where the object of study is socio-cultural-historical. History is everything related to the origins or stories about the formation/creation of something. just as we know, mathematics is the result of human thought, which has a long history to arrive at the form of mathematics we often find today. The existence of this history of mathematics needs to be known and studied. Because through the history of mathematics, we can know and understand the nature and essence of mathematics. Apart from that, we can also find out the cause of a proposition or the benefits of a concept in mathematics. Through the history of mathematics, we can see that mathematics has made quite a contribution to other fields of science. Mathematics became the basis for the birth of a new science, such as astronomy.Keywords: History, Mathematics, Mathematical Scientist